PENGARUH PENERAPAN PP NO 23 TAHUN 2018 TERHADAP PENINGKATAN KEPATUHAN PEMBAYARAN PAJAK PADA PELAKU UMKM (USAHA MIKRO KECIL MENENGAH) - Adiman, Sumardi; Rizkina, Miftha (JURNAL PERPAJAKAN, 2025)
Usaha Mikro, Kecil dan Menengah (UMKM) that have grown so rapidly from year to year have created tax obligations for these business actors. To help UMKM Taxpayers, the government in 2013 has issued Peraturan Pemerintah (PP) number 46. After several years of implementation, now the government has issued an improvement to the regulation, namely by issuing Government Regulation No. 23 of 2018. This regulation was issued to provide tariff relief for UMKM business actors. However, the PP which was passed in mid-2018 is still felt to lack to increase compliance in tax payments to UMKM. This research focuses on taxpayers' understanding of the implementation of these rules. This study aims to see the influence of PP 23 of 2018 related to the reduction of tax rates for UMKM, whether this reduction in tariffs can increase the compliance of UMKM actors in paying their tax obligations. The method used in this study uses a qualitative approach, steps in qualitative data analysis through four processes, namely collecting data, sorting unnecessary data, presenting and analyzing data, and finally concluding data. The result of this study is that all respondents stated that they were willing to pay taxes at the new rate. However, respondents hope to get more detailed information and guidance to take care of their tax obligations.